USLUB AL-KINAYAH: MAKNA ẒĀHIR DAN MAKNA BĀṬIN - Iyasyah Latuconsina; Muhammad Harjum; M. Fatkhul Ulum (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to analyze kināyah as a rhetorical device in Arabic balāghah, particularly within ʿilm al-bayān, in order to explain its forms, functions, and applications in the Qur’an, Hadith, and classical Arabic literature. This research employs a qualitative descriptive method using documentation techniques, with data sourced from clas-sical rhetorical works and primary religious texts. Data analysis is conducted by identifying kināyah expressions, examining their literal meanings, and interpreting their implied meanings based on contextu-al, linguistic, and theological perspectives. The results indicate that kināyah functions not only to beautify language but also to maintain politeness, convey sensitive meanings indirectly, and enrich semantic depth. Moreover, kināyah plays a strategic role in religious and liter-ary discourse by presenting ethical messages in a refined manner, demonstrating that it is an essential rhetorical element in effective Arabic communication.